Multicultural Personality of Professional Counselor Candidates: Evidence from Rasch DIF Analysis - Suciani Latif; M. Fiqri Syahril; Muh Ilham Bakhtiar; Akbar Na’im Fadhlillah; Saltanat Meiramova (State Islamic University (UIN) Salatiga, 2026)
This study examined the multicultural personality profile of professional counselor candidates and the gender fairness of the Multicultural Personality Questionnaire–Short Form (MPQ-SF). Using a quantitative descriptive design with Rasch-based psychometric analysis, the study involved 90 students from the Guidance and Counseling Teacher Professional Education Program (Pendidikan Profesi Guru Bimbingan dan Konseling [PPG BK]) at Universitas Negeri Makassar, comprising 20 males and 70 females with a mean age of 25.01 years. Data were collected using the 40-item MPQ-SF, which measures cultural empathy, flexibility, social initiative, emotional stability, and open-mindedness. Descriptive results showed relatively strong cultural empathy, flexibility, and open-mindedness, while social initiative and emotional stability remained moderate. After six misfitting persons were excluded, the final Rasch calibration was conducted with 84 respondents and showed acceptable psychometric quality, including person reliability of .89, item reliability of .96, raw variance explained by measures of 38.0%, and unexplained variance in the first contrast of 8.2%. Gender-based Differential Item Functioning (DIF) analysis indicated that most items functioned comparably across groups, although five items (14, 24, 25, 34, and 36) showed significant DIF. These findings suggest that the MPQ-SF provides a useful multicultural personality profile for counselor candidates, but gender-sensitive items require cautious interpretation. Future studies should involve more diverse samples and examine additional DIF sources, including ethnicity.